Implementation of the Islamic Education Curriculum in the Formation of Student Character in Madarasah Ibtidaiyah - Mursal Aziz; Dedi Sahputra Napitupulu; Bagus Purnomo (Sekolah Tinggi Ilmu Tarbiyah Madani Yogyakarta, 2025)
Student character building is one of the main goals of national education, especially in the context of Islamic education, which emphasizes not only cognitive aspects but also the formation of values and morals. However, modern challenges such as moral degradation, the influence of digital media, and weak social environmental control require educational institutions, especially madrasas, to implement the curriculum holistically and contextually. This study aims to examine the implementation of the Islamic Education curriculum in shaping student character at MIS Al-Washliyah Sidua Dua North Labuhanbatu. This study uses a qualitative approach with a phenomenological research type. The research location was chosen because MIS Al-Washliyah is known to be consistent in instilling Islamic-based character values. Data sources consist of primary data (teachers, madrasah principals, students) and secondary data (curriculum documents, lesson plans, and records of religious activities). Data collection techniques include observation, interviews, and documentation studies. Data analysis was carried out using the Miles and Huberman model, while data validity was tested by triangulation and member checking. The results show that the Islamic Education curriculum at MIS Al-Washliyah is effectively integrated into students' daily learning and activities. The instilling of values such as discipline, responsibility, and honesty is achieved through religious practices, teacher role models, and Islamic school culture. The implications of this research indicate that successful character formation depends heavily on the implementation of a structured curriculum, supported by supervision, evaluation, and the involvement of all parties. These findings contribute to the development of an Islamic values-based character curriculum in madrasah.